Strategi Implementasi Nilai-Nilai Pendidikan Multikultural Dalam Pembelajaran Pendidikan Agama Islam di SMK Harapan Bangsa Panti - Ani, Ani; Charles, Charles; Aprison, Wedra; Wati, Salmi (Faidatuna, 2024)
With regards to carrying out the upsides of multicultural training at Harapan Bangsa Panti Professional Secondary School, this review endeavors to recognize the strategies utilized by Islamic strict instruction instructors. Perception, interview, and documentation information assortment procedures were utilized in this subjective exploration. The information examination approach stage incorporates information decrease, information show, information check, triangulation, and leading administrative interviews. The exploration discoveries show: At Harapan Bangsa Panti Professional School, each Islamic Strict Training instructor makes educational program and example plans as a feature of carrying out multicultural instruction values. The idea of multicultural schooling is utilized in Islamic Strict Training to establish an Islamic learning climate by imparting the upsides of respectability, ethical quality and pardoning.